Analisis Occupational Crime Terhadap Calo Anggaran Di Dewan Perwakilan Rakyat Republik Indonesia Periode 2009-2014: Universitas Islam Riau - Fakhri Usmita (UIR PRESS, 2019)
Some fissure of rule and unconsistency of implementation could be made of same certain people to achieve personal or group goals. Misuse of these failure could then sacrifice that institutions, society or evan nation. I argued that could have been due to the existence of people who, because of his work, knew of the gap, and made use of the symbolization of his work for the achievement of his or their own interests. This study found that there are misuse practice of authority by certain people (senate) in addition of budget fund for certain area, correlated with occupational crime. This kind of people use the facilities of their position to make it easer. Seeing these problem, this qualitative study is trying to illustrated that brokers activities in House of Representetif of Republic of Indonesia views of occupational crime by Clinard and Quinney.